4(x+2.19)=3x

Simple and best practice solution for 4(x+2.19)=3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2.19)=3x equation:


Simplifying
4(x + 2.19) = 3x

Reorder the terms:
4(2.19 + x) = 3x
(2.19 * 4 + x * 4) = 3x
(8.76 + 4x) = 3x

Solving
8.76 + 4x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
8.76 + 4x + -3x = 3x + -3x

Combine like terms: 4x + -3x = 1x
8.76 + 1x = 3x + -3x

Combine like terms: 3x + -3x = 0
8.76 + 1x = 0

Add '-8.76' to each side of the equation.
8.76 + -8.76 + 1x = 0 + -8.76

Combine like terms: 8.76 + -8.76 = 0.00
0.00 + 1x = 0 + -8.76
1x = 0 + -8.76

Combine like terms: 0 + -8.76 = -8.76
1x = -8.76

Divide each side by '1'.
x = -8.76

Simplifying
x = -8.76

See similar equations:

| a-25=-25 | | 200x-0.43=400x+0.03 | | x^2+16*x-438.4=0 | | 4.4x-27=2.9x+6 | | 67-20=2y-4 | | 4x(2+2)+4*6= | | 6y^2+28y-98=0 | | 3p-7=2(4-p) | | 5.6=10x+6.1 | | fx=3(2x-1) | | X/8+4=6 | | 1/4(8x-20)=1/3(15x-6) | | (3-7j)+(9-j)= | | Y-6.8=8 | | 2.5x+9-4.5x=1 | | 6-(6-10*343)= | | 9i/(8-5i) | | 5x-37.6=x | | x^2+16*x+1.2=0 | | 4(y+5)=32 | | 6m=2(5m+10) | | 0.5x+0.6=-1.9 | | [2(4-7)]= | | 3(2g+7)-6g-21=0 | | (x^4-y^4)*(x^4+y^4)=0 | | 2(x-8.8)=4.6 | | -12=4-21 | | 14x+93=261 | | 8=3x+4(-2x) | | 13-2(3x-6)=2(2-4x) | | 7x+5.03=4x+11 | | (x+3)*(x-4)=0 |

Equations solver categories